Detection of looseness degree of dental posts using natural frequency analysis. (August 2013) - Hsieh, Sung-Chih; Lin, Shu-Li; Huang, Yung-Kai; Chang, Wei-Jen; Yuan, Chia-Chun; Lo, Yi-June; Lee, Sheng-Yang; Huang, Haw-Ming
This study examines the relationship between the retention force and natural frequency of dental posts cemented with zinc phosphate cement. Forty-two decoronated maxillary incisors were collected and embedded in resin blocks. The 7-mm post spaces were prepared for all test samples prior to cementing the 13-mm Para-Posts with zinc phosphate cement. The natural frequency values and retention forces of the zinc phosphate cement–cemented Para-Posts in various liquid/powder mixing ratios were measured. Thereafter, the natural frequency values of the zinc phosphate cement–cemented posts were continuously detected during ultrasonic vibration. Moreover, both the natural frequency values and the dislodgement forces in response to ultrasonic vibrations were measured for the pretreated post samples. Results showed that the natural frequency values of the posts significantly decreased from 8.8 ± 0.8 to 5.0 ± 0.5 kHz ( P < 0.05) before and after ultrasound treatment, respectively. The natural frequency values and the dislodgement forces of tested posts had a highly linear relationship ( R 2  = 0.99, P < 0.05). These findings suggest that natural frequency is a variable for monitoring the stability status of zinc phosphate cement–cemented dental posts.